Pengaruh Perbandingan Na2SiO3 dan NaOH (0,5-1,5) pada Kadar Aktivator 0,43 terhadap Toughness Beton Geopolimer - Muhammad Hayyu ‘Alam (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Concrete typically consists of coarse aggregate, fine aggregate, cement, and water. However, cement production generates significant carbon dioxide emissions nearly equivalent to the tons of cement produced. One alternative to conventional concrete, which replaces cement as a binder, is geopolymer concrete. Geopolymer concrete utilizes fly ash or other materials containing silica and alumina as the binder. Unlike cement, which forms a binder through hydration, geopolymer concrete uses a chemical reaction with alkali activators such as Na2SiO3 (sodium silicate) and NaOH (sodium hydroxide). This study investigates the toughness of geopolymer concrete using cylindrical specimens measuring 15 cm x 30 cm with varying Na2SiO3 to NaOH ratios of 1:0.5, 1:1, and 1:1.5, cured at room temperature for 28 days. The study results show that the highest toughness was achieved with a sodium silicate to sodium hydroxide ratio of 1.5, yielding 2.7394 x 105 J/m3. Meanwhile, the toughness values for sodium silicate to sodium hydroxide ratios of 0.5 and 1.0 were 2.3748 x 105 J/m3 and 2.5821 x 105 J/m3, respectively. Thus, increasing the sodium silicate to sodium hydroxide ratio from 0.5 to 1.5 at an activator content of 0.43 affects the toughness of geopolymer concrete.